The nutritional effects of selected algae, prebiotics and commercial herbal feed additives on the growth rate and health of juvenile spotted grunter, Pomadasys commersonnii (Pisces: Haemulidae) - Mbona, Anathi (Department of Biological Sciences, 2018)
In the aquaculture of fish and shrimps, diets generally contain high levels of fish meal. Fish meal is a nutrient rich feed that contains essential amino acids and fatty acids, which are required to maintain optimum growth and health of an animal. It is traditionally used in aquaculture to promote feed efficiency, nutrient uptake and feed intake due to its high palatability and digestibility. Overexploitation of fisheries resources and the high growth rate of aquaculture industry, however, continues to put pressure on the supply of fish meal, thus increasing the demand and price of this sought-after product. The use of alternative ingredients to fish meal, therefore, remains a high priority for aquaculture nutrition. Hence, the aim of this was to investigate the physiological and developmental effects on juvenile spotted grunter, Pomadasys commersonnii, after supplementing fish meal with different feed additives for 12 weeks. One of the additives was then selected for further feeding at graded levels (increasing levels) for 8 weeks to ascertain whether fish meal could be replaced by higher amounts of the feed additive without negative consequences to the cultured spotted grunter.